Pharmacological management of panic disorder - Carlo Marchesi (Dove Medical Press, 2008)
Carlo MarchesiPsychiatric Section, Department of Neuroscience, University of Parma, Parma, ItalyAbstract: Panic disorder (PD) is a disabling condition which appears in late adolescence or early adulthood and affects more frequently women than men. PD is frequently characterized by recurrences and sometimes by a chronic course and, therefore, most patients require longterm treatments to achieve remission, to prevent relapse and to reduce the risks associated with comorbidity. Pharmacotherapy is one of the most effective treatments of PD. In this paper, the pharmacological management of PD is reviewed. Many questions about this effective treatment need to be answered by the clinician and discussed with the patients to improve her/his collaboration to the treatment plan: which is the drug of choice; when does the drug become active; which is the effective dose; how to manage the side effects; how to manage nonresponse; and how long does the treatment last. Moreover, the clinical use of medication in women during pregnancy and breastfeeding or in children and adolescents was reviewed and its risk-benefit balance discussed.Keywords: panic disorder, pharmacological treatment, treatment guidelines